Soluble Cluster of Differentiation 25 (sCD25) as a Predictor of Mortality of COVID-19 Patients in Surabaya, Indonesia - Harida Zahraini; Betty Agustina Tambunan; Bambang Pujo Semedi (Indian Journal of Forensic Medicine & Toxicology, 2022)
The purpose of this study was to analyze and determine the cut-off level of sCD25 as a predictor ofmortality in COVID-19 patients. In an observational analytic study with a prospective cohort design, thestudy population was COVID-19 patients who were hospitalized at RIK RSUD Dr. Soetomo Surabayafor the period July 2020-December 2020. Sampling was taken by consecutive sampling, divided intotwo groups, mild-moderate and severe-critical groups. The examination of sCD25 levels in both groupswas carried out on day-0 and day-6 of hospitalization using the sandwich ELISA method. The pairedgroup statistical analysis used the Wilcoxon range test, the unpaired group used the Mann WithneyU test. ROC curve analysis to determine the cut off level of sCD25 as a predictor of mortality. Therewere a total of 83 study patients consisting of 36 patients in the mild-moderate group, 47 patients inthe severe-critical group. There was a difference in sCD25 levels between mild-moderate COVID-19patients who were treated on day-6 compared to day-0, whereas in the severe-critical group there wasno difference in sCD25 levels. There was a difference in sCD25 levels in COVID-19 patients betweenthe mild-moderate group by severe-critical. The level of sCD25 with a cut off of 3.14 ng/mL (AUC0.719, p = 0.001) can be used as a predictor of mortality in COVID-19 patients with a sensitivity of96.2%, a specificity of 47.4%. Levels of sCD25 >3.14 ng/mL can be used as a predictor of mortality inCOVID-19 patients